Management of Atypical Cranial Meningiomas, Part 1: Predictors of Recurrence and the Role of Adjuvant Radiation After Gross Total Resection. Issue 4 (12th June 2014) - Sun, Sam Q.; Kim, Albert H.; Cai, Chunyu; Murphy, Rory K.J.; DeWees, Todd; Sylvester, Peter; Dacey, Ralph G.; Grubb, Robert L.; Rich, Keith M.; Zipfel, Gregory J.; Dowling, Joshua L.; Leuthardt, Eric C.; et al.
Abstract: BACKGROUND: Indications for external beam radiation therapy (EBRT) for atypical meningiomas (AMs) remain unclear. OBJECTIVE: To analyze features associated with recurrence in AM patients after gross total resection (GTR) and to assess the relative benefit of EBRT in a retrospective cohort study. METHODS: One hundred fifty-one primary AMs after GTR (88 female patients; median follow-up, 45.0 months) were examined for possible predictors of recurrence (age, sex, location, volume, bone involvement, brain invasion). The Fisher exact and Wilcoxon rank-sum tests were used to analyze the association between these predictors and use of EBRT. The impact on recurrence for these predictors and EBRT was analyzed with Kaplan-Meier and Cox regression. RESULTS: Of 151 patients, 13 (8.6%) experienced recurrence after GTR (median, 47.0 months). Multivariate analysis identified elevated mitotic index ( P = .007) and brain invasion ( P = .002) as predictors of recurrence. Larger volume ( P = .96) was not associated with recurrence but was more likely to prompt EBRT ( P = .001). Recurrences occurred in 11 of 112 with GTR (9.8%; median, 44 months) and 2 of 39 with GTR/EBRT (5.1%; median, 133 months). The 2-, 5-, and 10-year progression-free survival rates after GTR vs GTR/EBRT were 97%, 86%, and 68% vs 100%, 100%, and 78%. Kaplan-Meier analysis demonstrated no difference in progression-free survival or overall survival after GTR vs GTR/EBRT ( P = .8, P > .99). CONCLUSION: Brain invasion and high mitotic rates may predict recurrence. After GTR of AMs, EBRT appears not to affect progression-free survival and overall survival, suggesting that observation rather than EBRT may be indicated after GTR.